Development of a broadly active influenza intranasal vaccine adjuvanted with self-assembled particles composed of mastoparan-7 and CpG - Ontiveros-Padilla, Luis; Batty, Cole J.; Hendy, Dylan A.; Pena, Erik S.; Roque, John A.; Stiepel, Rebeca T.; Carlock, Michael A.; Simpson, Sean R.; Ross, Ted M.; Abraham, Soman N.; Staats, Herman F.; Bachelder, Eric M.; et al. (Frontiers in Immunology, 2023)
New vaccine adjuvants are needed due to limitations of currently licensed adjuvants. Mast cells (MC) are emerging as a target of a new class of mucosal vaccine adjuvants. Here we developed and characterized a nanoparticulate adjuvant comprised of a MC-activator (mastoparan-7 (M7)) and a TLR-ligand (CpG). This novel nanoparticle (NP) adjuvant was co-formulated with a computational optimized broadly reactive antigen (COBRA) for hemagglutinin (HA) that is broadly reactive against influenza strains. M7 was combined at different ratios with CpG and tested for in vitro immune responses and cytotoxicity. We observed significantly higher cytokine production in dendritic cells and MCs with the lowest cytotoxicity at a charge neutralizing ratio of nitrogen/phosphate = 1 for the M7 and CpG. This combination formed spherical-NPs around 200 nm with self-assembling capacity. Mice were vaccinated intranasally with COBRA HA and M7-CpG NPs in a prime-boost-boost schedule. Vaccinated mice had significantly higher antigen-specific antibody response (IgG, IgA) in serum and mucosa in comparison with controls. Splenocytes from vaccinated mice had significantly increased cytokine production upon antigen recall and showed the presence of central and effector memory T cells in draining lymph node (dLN). Finally, the co-immunization of NPs and COBRA HA were able to induce influenza H3N2-specific HAI antibody titers across multiple strains and partially protected mice from a challenge against an H3N2 virus. This illustrates that this NP adjuvant combination can induce a protective immune response with a broadly reactive influenza antigen via mucosal vaccination.